Nalar Atensi Pemilihan Perguruan Tinggi Islam di Program Studi FTIK UIN K.H Achmad Shiddiq Jember - Efendi, Erfan; Rozzaq, Abd (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The distinction between public and religious campuses often occurs in the community, the dividing barrier between the two has implications for the favorite attention of the nation's generation in choosing universities, and campuses based on religion are always superior. However, in the traces of developments at the State Islamic University KH. Achmad Siddiq has made significant progress every year, and the increasing interest of prospective students is forced to reject many applicants. It is the main attraction of this research for Then answer how the progress occurred. This research is a type of qualitative research, as a bridge so that the results are more in-depth the author will use integrative theory and approach the problem above with a psycho-sociological approach. The focuses that will be studied include; How is the pre-attention anomaly of new students in the Faculty of Tarbiyah and Teacher Training at UIN Jember? What is the process of reasoning? And the new paradigm of attention is developing? The results showed that the attention paradigm that emerged was the reasoning that was built after the anomaly and crisis in the selection of Islamic universities, there were three adjustment processes, namely economical commensurability, formal education commensurability, and moral commensurability. All three are carried out using a negotiation process of general expectations and the impact of anomalies which are believed to be a necessity of the era.